2007
DOI: 10.1021/jp075636s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the O + HCNO Reaction

Abstract: The kinetics of the O + HCNO reaction were investigated by a relative rate technique using infrared diode laser absorption spectroscopy. Laser photolysis (355 nm) of NO2 was used to produce O atoms, followed by O atom reactions with CS2, NO2, and HCNO, and infrared detection of OCS product from the O + CS2 reaction. Analysis of the experiment data yields a rate constant of k1= (9.84 +/- 3.52) x 10-12 exp[(-195 +/- 120)/T)] (cm3 molecule-1 s-1) over the temperature range 298-375 K, with a value of k1 = (5.32 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 70%
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 70%
“…Our previous studies [2][3][4][5][6] show that HCNO is a highly reactive molecule. Many secondary reactions following the photolysis can therefore occur.…”
Section: Resultsmentioning
confidence: 97%
“…HCNO (fulminic acid) is the less stable isomer of isocyanic acid; the kinetics of several reactions involving HCNO has only recently been studied [3][4][5][6][7]. There is only one previous study of the photochemistry of HCNO, an infrared laser spectroscopic study from our laboratory that identified five separate photolysis channels in the 248 nm photodissociation of this molecule [8].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting signals were then converted to absolute concentrations using the peak−peak amplitudes and HITRAN line strengths. 38 In Figure 2, we show the yield of unlabeled 14 Assuming that all of the detected 14 N 16 O (except for the HCNO photolysis background) originates from channel 1a, we can estimate a branching fraction into 1a by comparing the yield of 14 In a second series of experiments, we attempted to detect HCN products from channel 1b, using a newly acquired laser diode at ∼3250 cm −1 . The lower panel of Figure 1 shows HCN transient signals with and without the ICN precursor.…”
Section: Resultsmentioning
confidence: 99%